Reduction of Chemical Oxygen Demand (COD) and Total Suspended Solids (TSS) from Wastewater of Tapioca Plant Using Aluminium Sulfate and Poly Aluminium Chloride (PAC) as a Coagulant - Shinta Desnia Amalia Hidayati; Neni Damajanti (Research in Chemical Engineering, 2022)
Water is the source of life on the surface of the earth. But often the water used for life contains many organic compounds that are harmful to life. This is due to contamination of water sources by compounds from many places, one of which is waste from the tapioca industry. One method that can be used to reduce water pollution is the coagulation process using certain coagulants. The ability of Poly Aluminium Chloride (PAC) and aluminum sulfate as coagulant is utilized in the processing of tapioca wastewater to reduce COD and TSS levels. This study aims to determine the effect of coagulant dose and flocculation time on decreasing COD and TSS levels in tapioca wastewater from Purbalingga Aci Factory. The method used is coagulation using PAC and aluminum sulfate as a coagulant with a variation of the coagulant dose of 2000; 4000; 6000; 8000 and 10,000 mg/L as well as variations in flocculation time 25; 30; 35; 40 and 45 minutes. The results showed that the coagulant dose and flocculation time had an effect on decreasing COD and TSS in tapioca wastewater. The best use of PAC coagulant at a dose of 6000 mg/L with a flocculation time of 45 minutes, namely the COD value of 375.2 mg/L and TSS 110 mg/L. While the best use of aluminum sulfate coagulant at a dose of 8000 mg/L with a flocculation time of 45 minutes, namely the COD value of 203.2 mg/L and TSS 590 mg/L